1998
DOI: 10.1097/00005392-199808000-00047
|View full text |Cite
|
Sign up to set email alerts
|

Cd34 Immunohistochemical Assessment of Angiogenesis as a Prognostic Marker for Prostate Cancer Recurrence After Radical Prostatectomy

Abstract: Microvascularity or neovascularity as measured by the CD34 antigen may be a prognostic marker of recurrence for prostate cancer patients after radical prostatectomy but more study in prostate specific antigen era patients with sufficient followup is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 20 publications
2
58
0
3
Order By: Relevance
“…The recently reported strong association of high macrophage index with a better post-operative outcome in prostate cancer patients contrasts the postulated 'angiogenic role' of macrophages (Shimura et al, 2000). High angiogenesis is an important variable of poor prognosis in prostate carcinomas, as has been convincingly shown in a large number of studies (Silberman et al, 1997;Bettencourt et al, 1998;Borre et al, 1998;Strohmeyer et al, 2000;Mehta et al, 2001). Specific intratumoural conditions (cytokines released by cancer cells, fibroblasts or even by tumour related lymphocytes) may form a complex code that switches on/off or even reverses the macrophage angiogenic machinery.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 81%
See 1 more Smart Citation
“…The recently reported strong association of high macrophage index with a better post-operative outcome in prostate cancer patients contrasts the postulated 'angiogenic role' of macrophages (Shimura et al, 2000). High angiogenesis is an important variable of poor prognosis in prostate carcinomas, as has been convincingly shown in a large number of studies (Silberman et al, 1997;Bettencourt et al, 1998;Borre et al, 1998;Strohmeyer et al, 2000;Mehta et al, 2001). Specific intratumoural conditions (cytokines released by cancer cells, fibroblasts or even by tumour related lymphocytes) may form a complex code that switches on/off or even reverses the macrophage angiogenic machinery.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 81%
“…Once activated by these stimuli, endothelial cells proliferate, migrate and, eventually, differentiate into functioning capillaries (Pinedo and Slamon, 2000). In prostate carcinomas, as in other tumours, an increased angiogenesis, assessed as microvessel density (MVD), is usually connected with poor prognosis (Hall et al, 1994;Bettencourt et al, 1998;Offersen et al, 1998;Strohmeyer et al, 2000a,b).…”
mentioning
confidence: 99%
“…Some authors (8,21,22) have established a quantitative relationship between tumor neovascularization with recurrence and progression in prostate cancer, although others have not found correlation with clinical outcome (23). Tumor microvessel density/vascular endothelial growth factor expression has also been shown to predict biologic behavior in prostatic cancer (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…16 Any dark staining endothelial cell or cell cluster clearly separate from adjacent structures was considered a single vessel. For practical purposes, tumors were arbitrarily divided into two groups: one with microvessel counts less than or equal to 90 per 2006microscopic field ( Figure 1A), the second with microvessel counts superior to 90 per 2006microscopic field 15 ( Figure 1B). This two-level classification of density was made independently by two researchers (MS and NC) without knowledge of the clinical course of the disease.…”
Section: Methodsmentioning
confidence: 99%
“…13 -15 In more recent studies it has also been demonstrated that CD34 quantifies MVD in PC and that it can be useful to identify patients at high-risk of recurrence after radical prostatectomy. 15 The purpose of the present study was to see whether there is a correlation between MVD, assessed by the analysis of CD34 immunoreactivity and disease recurrence (biochemical or clinical) in a series of patients who underwent radical prostatectomy (RP).…”
Section: Introductionmentioning
confidence: 99%